Rapid room temperature synthesis of red iridium(iii) complexes with Ir–S–P–S structures for efficient OLEDs. Issue 23 (21st May 2019) - Su, Ning; Yang, Hui-Qing; Shen, Cheng-Zhen; Yan, Zhi-Ping; Chen, Zhao-Xu; Zheng, You-Xuan
Abstract : Two red iridium(iii ) complexes with Ir–S–P–S structures were obtained rapidly at room temperature in 5 min with high yields, and their devices achieve good performances with a maximum external quantum efficiency of 24.90%. Abstract : Due to the strong coordination ability between sulfur and iridium atoms, O, O -diphenyl S-hydrogen phosphorodithioate acid (opss) and O, O -di(naphthalen-1-yl) S-hydrogen phosphorodithioate acid (onss) were applied as ancillary ligands in two red iridium(iii ) complexes. Both complexes, (tfmpqz)2 Ir(opss) and (tfmpqz)2 Ir(onss), with Ir–S–P–S four membered ring structures were obtained rapidly at room temperature in 5 min with high yields, in which 4-(4-(trifluoromethyl)phenyl)-quinazoline (tfmpqz) was used as the main ligand, and the calculated Gibbs free energy changes of both complex formation reactions further prove that they are exothermic and thermodynamically beneficial processes. Both Ir(iii ) complexes show identical PL emissions at 600 nm with high phosphorescence quantum yields of 0.68 and 0.79, respectively. Using the two complexes as dopants, organic light emitting devices with the structure of ITO/HATCN (hexaazatriphenylenehexacabonitrile, 5 nm)/TAPC (bis(4-( N, N -ditolylamino)phenyl)cyclohexane, 30 nm)/(tfmpqz)2 Ir(opss) or (tfmpqz)2 Ir(onss): 26DCzppy (2, 6-bis-(3-(carbazol-9-yl)phenyl)pyridine) (12 wt%, 10 nm)/TmPyPB (1, 3, 5-tris((3-pyridyl)-phen-3-yl)benzene, 30 nm)/LiF (1 nm)/Al (100 nm) achieve good performances. Especially, due to a larger conjugated degree of the (tfmpqz)2 Ir(onss) complex, its device exhibits better device performances with a maximum luminance of 52 030 cd m −2, a maximum current efficiency of 57.98 cd A −1, a maximum power efficiency of 44.40 lm W −1 and a maximum external quantum efficiency of 24.90%.